(untitled) (NAU Journal of Library and Information Science, 2022)
The main purpose of this study was to assess the perceived impact of information literacy skills on College of Education students’ effective use of library resources in Anambra State. Three research questions guided the study. Descriptive survey research design was adopted for the study. Population of the study comprised one thousand, three hundred and four year two and three students in the two Colleges of Education studied. The sample size was three hundred and six students, selected through proportionate stratified random sampling technique. Research instrument titled Information Literacy Skill Test was the instrument used for data collection. Data collected were analysed using frequencies and simple percentage. The findings of the study indicate that only one skill out of the ten skills listed in the instrument was possessed by the students. None of the ten required skills in information synthesis was possessed by the students. Furthermore, none of the ten skills in information evaluation was possessed by students in the Colleges of Education in Anambra State. This suggests that the College of Education students in Anambrs State cannot effectively utilize their library resources. Based on the findings, it was recommended that the Management of College of Education should develop a course outline on information literacy to be included in the academic curriculum of the institution.